2011
DOI: 10.1001/archinternmed.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Benefits and Harms on Older Persons' Willingness to Take Medication for Primary Cardiovascular Prevention

Abstract: Background Quality-assurance initiatives encourage adherence to evidenced-based guidelines based on a consideration of treatment benefit. The objective of this study was to examine older persons’ willingness to take medication for primary cardiovascular disease prevention according to benefits and harms. Methods In-person interviews were performed with 356 community-living older persons. Participants were asked about their willingness to take medication for primary prevention of myocardial infarction (MI) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(138 citation statements)
references
References 36 publications
(39 reference statements)
6
125
0
1
Order By: Relevance
“…[8][9][10][11] In addition, prognosis impacts the likelihood of benefits and harms arising from tests or treatments with up-front harms and delayed benefits, such as cancer screenings 12,13 or medications targeted at risk factor reduction. 14 When shared with patients, prognostic information may also facilitate greater patient involvement in medical decision-making. [15][16][17][18][19] Despite evidence suggesting that prognosis is an important tool in the care of older adults with late-life disability, we know very little about the preferences for discussing prognostic information in this population.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] In addition, prognosis impacts the likelihood of benefits and harms arising from tests or treatments with up-front harms and delayed benefits, such as cancer screenings 12,13 or medications targeted at risk factor reduction. 14 When shared with patients, prognostic information may also facilitate greater patient involvement in medical decision-making. [15][16][17][18][19] Despite evidence suggesting that prognosis is an important tool in the care of older adults with late-life disability, we know very little about the preferences for discussing prognostic information in this population.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a recent study reported that adherence to cardiovascular preventive medications can be hindered because of a complex regimen with multiple medications taking and multiple dosing schedules [16] . Additionally, adverse effects and low perceptions of medicinal efficacy of cardiovascular drugs may profoundly affect adherence [17] . Promotion of adherence to medications taking need to address drugs used for each chronic condition, adverse effects, and perceptions of drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Of those willing to take the medication (n = 313), only 13.7% (n = 43) said that they would change their minds about taking the drug if the MI risk were reduced from 10 to 7 (i.e., just 3 MIs prevented). 34 In contrast, medication-taking decisions were strongly associated with concerns about adverse effects. Of the 313 who expressed willingness to take medication in the initial scenario, the proportions who remained willing to take the medication when told that it would result in daily fatigue and dizziness, daily mild to moderate nausea, and daily fuzzy or slowed thinking were 52%, 35%, and 31%, respectively.…”
Section: How Do Seniors Respond To 100% Cost-sharing For Prescriptionmentioning
confidence: 99%
“…Fried et al commented on the "notable" finding that in response to the initial scenario in which respondents were told that a drug would have no adverse effects, 13 (31%) of 42 respondents who expressed either uncertainty or unwillingness to take the drug told the investigators that they did not believe that the drug would actually have no adverse effects, and 7 (17%) said that they disliked medications. 34 Information about other nonfinancial factors affecting medication adherence is somewhat limited. For example, Ingersoll and Cohen (2008) conducted a systematic review of the literature on the relationship between drug regimen characteristics and adherence to treatment for multiple chronic diseases.…”
Section: How Do Seniors Respond To 100% Cost-sharing For Prescriptionmentioning
confidence: 99%